2021
DOI: 10.1080/02640414.2021.1874160
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and burden of health problems in competitive adolescent distance runners: A 6-month prospective cohort study

Abstract: Objectives: To describe all health problems (injuries and illnesses) in relation to type, location, incidence, prevalence, time loss, severity, and burden, in competitive adolescent distance runners in England. Design: Prospective observational study. Methods: 136 competitive adolescent distance runners (73 female athletes) self-reported all health problems for 24-weeks between May and October 2019. Athletes self-reported health problems using the Oslo Sports Trauma Research Center Questionnaire on Health Prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 39 publications
(48 reference statements)
1
29
3
Order By: Relevance
“…This is further supported by the absence of a rate ratio between the male and female participants in this study (rate ratio = 0.89; 95% CI: 0.68–1.33). Despite these observations, these figures are notably lower than those reported in a recent study that included a similar cohort of adolescent distance runners (Mann et al, 2021 ). Nonetheless, comparison between these studies is challenging due to the different study designs (i.e., retrospective vs. prospective).…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…This is further supported by the absence of a rate ratio between the male and female participants in this study (rate ratio = 0.89; 95% CI: 0.68–1.33). Despite these observations, these figures are notably lower than those reported in a recent study that included a similar cohort of adolescent distance runners (Mann et al, 2021 ). Nonetheless, comparison between these studies is challenging due to the different study designs (i.e., retrospective vs. prospective).…”
Section: Discussioncontrasting
confidence: 74%
“…When considering exposure time, the reported IR (6.3/1,000 participation hours), for “all RRI,” was slightly higher than that reported in two distinct cohorts of elite Swedish adolescent distance runners (4.0 to 5.3/1,000 participation hours) (von Rosen et al, 2017 , 2018 ). The reported IR for “all RRI” was lower than that reported in a previous study on a cohort of competitive adolescent distance runners in England (25.0/1,000 participation hours) (Mann et al, 2021 ), alongside previous studies that have included cohorts of recreational (7.7/1,000 participation hours) and novice (17.8/1,000 participation hours) adult distance runners (Videbaek et al, 2015 ). Overall, these IP and IR findings suggest that the cohort of competitive adolescent distance runners in the present study maintain a greater training volume (exposure) than in other sports, whereby the higher IP may be a result of this greater training volume.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Of the 35 injury prevention articles reviewed that used the term "adolescent" in the title, only 17% (N 5 6) reported using a measure of biological age. [40][41][42][43][44][45] Two articles assessed maturation by estimating the time from peak height velocity (PHV) using the equation developed by Moore et al while Holden et al assessed landing kinematics of 184 adolescent male and female athletes (mean age 13 6 0.3 years) during the growth spurt. 41,46 Holden et al 41 classified participants as pre-PHV or mid PHV into an early puberty group and those as post-PHV into a late puberty group.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of health service provision to adolescent athletes originate from the U.S., where 2 million injuries, 500,000 physician visits, and 30,000 hospitalizations have been reported to occur each year among high school athletes [ 10 ]. Detailed epidemiological data on young competitive athletes’ injuries from other countries are limited and often restricted to single sports [ 11 , 12 , 13 , 14 ]. However, a broad health evaluation among Italian Youth Olympics participants representing all sports revealed that 12% had a condition warranting medical attention (mainly cardiovascular (4.5%) or pulmonary (4.5%)) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%